Numerical simulation of titanium fibre metallic laminates under various impact loading - Selvadurai Shanmugasundram (2017)
This thesis is linked to the research project carried out for the development of multi-functionally hierarchical Fiber-Metal Laminates (FMLs) for impact protection. The objective is to study impact behaviour of the Titanium (Ti) ICarbon fibre reinforced plastics (CFRP). The current study focuses on the finite element analysis of Titanium (Ti) I Carbon Fiber Reinforced Plastics (CFRP) composite for various impact velocity to investigate the strength and energy absorbing capabilities of the hybrid composite and to validate the experimental results. From the past researches on the FML composites, it has been found that Titanium (Ti)/CFRP composite has attractive mechanical properties such as high hardness and high elastic modulus which makes it a suitable candidate for aerospace and other applications. The experimental tests for the impact analysis are completed and documented by Assoc Prof. CHAI GIN BOAY and his team at Nanyang Technological University. Two tasks have been examined in this study. Part I investigates the effect of the low velocity impact on the composite panel. Low velocity impact was conducted for three different samples with different impact energies. From the experimental results, it was found that with increase in impact energy, the deformation of the composite panel has increased significantly. The permeant deformation and the bulge formation on both side of the composite panel are compared among the three different samples. The force for the initial crack propagation of titanium sheet is decreased because of less energy dissipated through the deboning between metal and composite layer. The high strength of bonding between titanium sheet and composite layer help to arrest the cracks. Part II is detailing about the dynamic failure of the composites due to ballistic impact velocities ranging from 100-400 m/s. In low impact velocity impact, the front and back panels failed in a petaling shape mode but when the impact velocity is increased to the ballistic level of 400m/s shear plugging was observed. The experimental setup is replicated in the FE model and analyzed for the same velocity and energy levels for both low and high velocity impacts models. From the numerical simulation, it was that the observed deformation and energy levels are comparable with the experimental testing. Keywords: FML, Ballistic, Low velocity, FE modelling